Trampoline Park Injuries and Their Burden on Local Orthopaedic and Emergency Services - Stevan Jordan; Roozbeh Shafafy; Amelia Davidson; Christopher To; Kathryn Gill; Matthew Solan (Bulletin of Emergency and Trauma, 2019)
Objective: To investigate the incidence of trampoline park injuries (TPIs) at a local recreational facility and to quantify the burden on emergency and orthopaedic services at our institute.Methods: All patients that presented to the Emergency Department (ED) from the trampoline park via ambulance from July 2014 to November 2015 were included in the study. Patients’ medical records were reviewed for clinical details including date, location and type of injury, treatment received, length of stay and outpatient follow-up. A cost analysis was performed to estimate the financial impact of each injury.Results:  A total of 71 patients were included in the study, with a mean age of 20 (7-48). Soft tissue sprains (n=29, 41%) and fractures (n=25, 35%) were the most common injuries, with the majority occurring in the lower limb. Two patients sustained open tibial fractures necessitating transfer to level 1 trauma centres. Fourteen patients (20%) underwent surgery, predominantly requiring open reduction and internal fixation. Overall, 18 patients (25%) required admission to hospital with mean length of stay of 2 days. The cost for pre-hospital, emergency and in-patient care amounted to over £80,000.Conclusion: TPIs pose a significant financial cost for local orthopaedic and emergency services. Contrary to studies evaluating home trampoline injuries, the majority of fractures at trampoline parks occurred in the lower limbs. Improved injury prevention strategies are required to help reduce morbidity and lower the financial implications for local NHS trusts.